Segregation ratios of colored grains in F1 hybrid wheat - Guo,Zifeng (2012)
Nutritious and functional foods from wheat have received great attention in recent years. Colored-grain wheat contains a large number of nutrients such as anthocyanins and hence the breeding is interesting. In this work, colored-grained wheat lines of mixed pollination of einkorn wheat (Triticum boeoticum, AA) and French rye (French Secale cereale, RR) were used as male parents and wheat line Y1642 (derived from common wheat and Agropyron elongatum, AABBDD) was used as the female parent. These colored wheat were used for diallel cross to study the segregation ratios of F1 colored grains. Results show that the color inheritance of purple-grained wheat follows a maternal inheritance pattern and that the blue-grained wheat expresses xenia in most cases. In some circumstances, the grains with different color shades appear in the same spike.